Nanomedicine for drug delivery and therapeutics - Mishra, Ajay Kumar, 1965- (Hoboken, N.J. : Scrivener Publishing, 2013)
'This book describes a broad area of nanomedicine which involves mainly applications, diseases, and diagnostics. The comprehensive coverage provides researchers, academics, and health specialists with a great tool, that includes techniques applicable to various uses.'--
pt. 1. Nanomedicine -- pt. 2. Drug delivery and therapeutics.
Includes bibliographical references and index.
Keywords: Nanomedicine; Drug delivery systems; Therapeutics